A review on cationic starch and nanocellulose as paper coating components - Sharma, Mohit (2020)
Starch and derivatives thereof have proven their usefulness in paper coating processes. Among these derivatives, cationic starch has been widely used in the paper industry as a flocculation, dispersion and ink fixing agent. In another context, nanoscale cellulosic materials have been shown to improve the strength, retention of fillers, the barrier properties of packaging paper products, and printing qualities. This review summarizes the recent studies on the general components used in paper coating, describes the conventional and alternative synthetic processes of cationic starches and nanocellulose, and deals with their current and potential applications in papermaking, focusing primarily on surface treatments. Moreover, environmental applications have been considered to expand the understanding and usefulness of these materials. Further research on modified polysaccharides is encouraged to replace, in a feasible way, petro-based components of coating formulations, and to provide paper surfaces with new properties.